2022
DOI: 10.1001/jamahealthforum.2022.1702
|View full text |Cite
|
Sign up to set email alerts
|

US Hospital Characteristics Associated With Price Transparency Regulation Compliance

Abstract: had full access to all of the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 4 publications
2
19
0
Order By: Relevance
“…Third, we were unable to obtain the trauma activation fees for 3.3% of eligible trauma centers; however, the fact that we were unable to obtain the trauma activation fees for some facilities is itself useful information because all hospitals are supposed to make these data publicly available. As we and several other researchers have noted, hospitals do not universally provide these data. Fourth, we only assessed the trauma activation fees for trauma centers that had been verified by the ACS, so our data may not be applicable to trauma centers only verified by their states.…”
Section: Discussionmentioning
confidence: 78%
“…Third, we were unable to obtain the trauma activation fees for 3.3% of eligible trauma centers; however, the fact that we were unable to obtain the trauma activation fees for some facilities is itself useful information because all hospitals are supposed to make these data publicly available. As we and several other researchers have noted, hospitals do not universally provide these data. Fourth, we only assessed the trauma activation fees for trauma centers that had been verified by the ACS, so our data may not be applicable to trauma centers only verified by their states.…”
Section: Discussionmentioning
confidence: 78%
“…5,7 Our own work has highlighted financial motivations such as market competition as a factor associated with compliance. 11 Our current study adds to this literature by reporting, to our knowledge, the largest academic assessment of hospital price transparency compliance for both 2021 and 2022. Our data are unique in that they have the highest degree of completeness (ie, the share of hospitals for which we locate price data), with compliance for each hospital in each year assessed multiple times by different researchers.…”
Section: Discussionmentioning
confidence: 79%
“…Other articles have examined hospital characteristics that correlate with compliance at a given time point . Our own work has highlighted financial motivations such as market competition as a factor associated with compliance …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies have found gradual increases in the proportion of hospitals complying with the new CMS requirements. 2,3 Other studies have found between-hospital variation in posted prices (eg, 20%-50% price differences) for the same service, suggesting potential opportunities for savings if patients were to select lower-cost facilities 4,5 ; such savings are particularly important for the 10% of individuals in the US who are uninsured, but also for other populations, such as those enrolled in high-deductible health plans. 6,7 However, the extent to which a hospital's prices posted online correlate with the prices they give to a telephone caller is unknown.…”
mentioning
confidence: 99%